Antioxidant Senotherapy by Natural Compounds: A Beneficial Partner in Cancer Treatment - Yulia Aleksandrova; Margarita Neganova (Antioxidants)
Aging is a general biological process inherent in all living organisms. It is characterized by progressive cellular dysfunction. For many years, aging has been widely recognized as a highly effective mechanism for suppressing the progression of malignant neoplasms. However, in recent years, increasing evidence suggests a “double-edged” role of aging in cancer development. According to these data, aging is not only a tumor suppressor that leads to cell cycle arrest in neoplastic cells, but also a cancer promoter that ensures a chronic proinflammatory and immunosuppressive microenvironment. In this regard, in our review, we discuss recent data on the destructive role of senescent cells in the pathogenesis of cancer. We also identify for the first time correlations between the modulation of the senescence-associated secretory phenotype and the antitumor effects of naturally occurring molecules.